Single-mode pumping scheme for EDFA with high-power conversion efficiency using a 980-nm Ti : S laser - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Ahmad, Harith (John Wiley & Sons, 2006)
In this paper, we demonstrate a high-power erbium-doped fiber amplifier pumped by single-mode titanium sapphire (Ti:S) laser at 980 nm. The highest output power of 22.6 dBm is measured at 1549 nm with an input signal power of 4 dBm and a pump power of 300 mW. This corresponds to power-conversion efficiency (PCE) of 60, providing 95 quantum efficiency. The experimental results show the feasibility of using a single-mode laser from a high-power semiconductor chip to produce high-efficiency booster amplifiers. (c) 2005 Wiley Periodicals, Inc.